Предмет: Алгебра,
автор: gennadiy2288
2(x+2)+2x=12,3(x+3)+6=13x,4x+6x-7=12,x*(2-x)=-x^2+4+5 через запятую другие примеры помогите пж
Ответы
Автор ответа:
0
Объяснение:
2(х+2)+2х=12
2х+4+2х=12
4х=12-4
4х=8
х=8/4
х=2
3(х+3)+6=13х
3х+9+6=13х
3х-13х=-9-6
-10х= -15
х=1,5
4х+6х-7=12
10х=12+7
10х=19
х=1,9
х(2-х)=х^2+4+5
2х-х²= 2х+9
2х-2х-х²= 9
-х²=9
Похожие вопросы
Предмет: Русский язык,
автор: renderfear
Предмет: Другие предметы,
автор: антуан
Предмет: Українська мова,
автор: Аноним
Предмет: Математика,
автор: Юрик456456446
Предмет: Литература,
автор: MaRuSkA000LoVe